Anarchism Movement As Depicted In Erin Gruwell's The Freedom Writers Diary - Hakim, Luqman, Dr. M. Thoyibi, MS., Dr. Abdillah Nugroho, M. Hum (2016)
Erin Gruwell's The Freedom Writers Diary is a book which highlights the problem that occurs in American education. It does not just shows the reader how the education is run, but it presents the social condition of the education itself. It relates with some notable issues namely inequality, racial tension and class struggle which then were explored with Anarchism perspective. Therefore this research investigates what characteristics and indicators of Anarchism are described in the Freedom Writers Diary, how the depiction of Anarchism is described, and how the effect of the Freedom Writers Diary to the larger society is revealed. In conducting this research, this research applied descriptive qualitative research. The data of this research was taken from the dialogues and statements in the book and from other sources. The instrument of this research is the researcher himself who collects, analyzes, and presents the data findings of the research then draws the conclusions. The result of the analysis shows: (1) The anarchism characteristics in the Freedom Writers Diary are Liberty, Equality and Solidarity. (2) There are eight indicators of characteristics of Anarchism. (3) The Anarchism is depicted in the Freedom Writers Diary through the plot, character and characterization and the author's style. (4) The release of the Freedom Writers Diary gives some effect to the larger society, it encourages the rise of tolerance and awareness of disadvantaged students.